If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + 1 = -7 + 4n Reorder the terms: 1 + 6n = -7 + 4n Solving 1 + 6n = -7 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 1 + 6n + -4n = -7 + 4n + -4n Combine like terms: 6n + -4n = 2n 1 + 2n = -7 + 4n + -4n Combine like terms: 4n + -4n = 0 1 + 2n = -7 + 0 1 + 2n = -7 Add '-1' to each side of the equation. 1 + -1 + 2n = -7 + -1 Combine like terms: 1 + -1 = 0 0 + 2n = -7 + -1 2n = -7 + -1 Combine like terms: -7 + -1 = -8 2n = -8 Divide each side by '2'. n = -4 Simplifying n = -4
| 10=35t-16t^2 | | -4(3x-3)+7x=5(x+4) | | 5-4n=-13+2n | | 4x+1+3x+12=34 | | 4x+34+3x+77=6x+23+4x+64 | | (2x+3)+(5x+5)= | | 8-8b=8+2b | | 64xc=832 | | 2(x-12)-4x=2(-x+3)-18 | | 8+3n=-7+8n | | 7x+4y=366 | | 7v+3=-1+5v | | 8(2x-1)=3(4x+8)+4 | | t=35t-16t^2 | | -2(4+p)=-18 | | E=4x(7+3x) | | 3x^2y^2+6x^2y-9xy= | | -5.7x-1.9y=11.4 | | (7x+3)+(9n+3x)+(-2-2n)= | | 5+7x=-4 | | -38=-2(-4ed-24) | | -30=-6(5+p) | | 6x+15=3y-3 | | -3(-x)-7=1+x | | 28=f-3 | | 6000=4 | | 6(p-8)=-42 | | -30+(150)=X | | 24=2(-x+3) | | 2(3y+4+2)= | | 17+10x-3=-3(x-6) | | 14x+8+10x+28=180 |